2012
DOI: 10.1177/1076029611425829
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity of Various Thrombin Products With Anti-Rabbit Antibodies to Bovine, Human, and Recombinant Thrombin

Abstract: JMI-thrombin is used as topical hemostatic agent. While earlier clinically available JMI were reported to produce immunologic responses upon repeated exposure, the improved JMI, Recothrom?, and Evithrom? are claimed to be less immunogenic. Recothrom, despite its reduced immunogenic nature, upon repeated administration may result in the generation of antibodies (Abs) and that may cross react with bovine and human thrombin. Therefore, groups of rabbits were challenged repeatedly with Recothrom, Evithrom, and JMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Preimmune blood and antiserum were collected from each rabbit in serial order as shown previously. 20 The antiserum from each rabbit and the pooled antisera obtained from 3 individual rabbits in each treatment group were stored at −80ºC prior to IgG isolation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preimmune blood and antiserum were collected from each rabbit in serial order as shown previously. 20 The antiserum from each rabbit and the pooled antisera obtained from 3 individual rabbits in each treatment group were stored at −80ºC prior to IgG isolation.…”
Section: Methodsmentioning
confidence: 99%
“…Gel electrophoresis and Western blotting were carried out as described previously. 20 In brief, samples were denatured and subjected to electrophoresis through 4% to 20% gradient Tris-N-2-hydroxyethylpiperazine-N-2-ethanesulfonic acid–sodium dodecyl sulfate (SDS) polyacrylamide mini gels (Pierce Biotechnology, Rockford, Illinois) and then electrotransferred onto nitrocellulose membrane overnight at 4°C. Precision Dual Color Plus protein standards (Bio-Rad Laboratories) were included in each gel.…”
Section: Methodsmentioning
confidence: 99%
“…The 36-kDa band in the presence of generation of thrombin from prothrombin has been previously reported in a study to represent thrombin on the immunoblotting human and bovine thrombin. 27 In order to further investigate the effect of AryoSeven and NovoSeven preparations with final concentration of 0.25 and 0.5 mg/mL in 30-minute incubation time in generation of thrombin upon supplementation in activated Profilnine, immunoblotting studies were carried out. This study revealed a strong band at 36 kDa and a very faint band at 50 kDa, which were comparable in all products.…”
Section: Discussionmentioning
confidence: 99%
“…Preimmune blood and antiserum were collected from each rabbit in serial order as shown previously. 27 The antiserum from each rabbit and the pooled antisera obtained from 3 individual rabbits in each treatment group were stored at −80°C prior to IgG isolation.…”
Section: Methodsmentioning
confidence: 99%
“…Gel electrophoresis and Western blotting were carried out as described previously. 27 In brief, samples were denatured and subjected to electrophoresis through 4% to 20% gradient Tris-N-2-hydroxyethylpiperazine-N-2-ethanesulfonic acid–sodium dodecyl sulfate (SDS) polyacrylamide mini gels (Pierce Biotechnology, Rockford, Illinois) and then electrotransferred onto nitrocellulose membrane overnight at 4°C. Precision Plus Protein Dual Color standards (Bio-Rad Laboratories) were included in each gel.…”
Section: Methodsmentioning
confidence: 99%